2021
DOI: 10.3389/fonc.2021.682773
|View full text |Cite
|
Sign up to set email alerts
|

SPNS2 Downregulation Induces EMT and Promotes Colorectal Cancer Metastasis via Activating AKT Signaling Pathway

Abstract: Spinster homologue 2 (SPNS2), a transporter of S1P (sphingosine-1-phosphate), has been reported to mediate immune response, vascular development, and pathologic processes of diseases such as cancer via S1P signaling pathways. However, its biological functions and expression profile in colorectal cancer (CRC) is elusive. In this study, we disclosed that SPNS2 expression, which was regulated by copy number variation and DNA methylation of its promoter, was dramatically upregulated in colon adenoma and CRC compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
0
12
1
Order By: Relevance
“…These data reveal that CTSG absence exhibits cancer stimulative impacts through Akt/mTOR signaling pathway activation and Akt signaling pathway suppression by MK2206 abolishes CTSG silenced expression-induced up-regulation of Bcl2 and cell viability in vitro and in vivo . Moreover, SC79, an Akt activator, could promote cell proliferation and metastasis through positive regulation of Akt 35 - 37 . Our results also showed that up-regulation of CTSG reversed SC79-induced CRC cell proliferation ( Figure S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…These data reveal that CTSG absence exhibits cancer stimulative impacts through Akt/mTOR signaling pathway activation and Akt signaling pathway suppression by MK2206 abolishes CTSG silenced expression-induced up-regulation of Bcl2 and cell viability in vitro and in vivo . Moreover, SC79, an Akt activator, could promote cell proliferation and metastasis through positive regulation of Akt 35 - 37 . Our results also showed that up-regulation of CTSG reversed SC79-induced CRC cell proliferation ( Figure S7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our findings, a recent study suggests that SPNS2 expression was markedly lower in ten kinds of tumor (including breast invasive carcinoma) as compared to adjacent non-cancerous samples. The authors reported that the levels of SPNS2 were downregulated in colorectal cancer and were associated with poor differentiation, advanced pTNM stage and poor prognosis of the disease 52 . Being a S1P transporter, the levels of SPNS2 were found to be positively associated with SPHK1 expression in tumor tissue in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, low SPNS2 expression correlated with poor prognosis in CRC and ectopic expression of SPNS2 inhibited cell proliferation, migration, epithelial-mesenchymal transition, invasion, and metastasis in CRC cell lines. This appeared to be S1P independent, rather acting directly via inactivation of AKT signaling [142]. These data also need to be considered when proposing SPNS2 as a target to improve anti-tumor immunity and combat metastasis.…”
Section: S1p Export and Tumor Immunitymentioning
confidence: 95%